B and T Immunoregulation: A New Insight of B Regulatory Lymphocytes in Autism Spectrum Disorder - De Giacomo, Andrea; Gargano, Concetta Domenica; Simone, Marta; Petruzzelli, Maria Giuseppina; Pedaci, Chiara; Giambersio, Donatella; Margari, Lucia; Ruggieri, Maddalena (Frontiers in Neuroscience, 2021)
Autism Spectrum Disorder (ASD) is a heterogeneous neurodevelopmental disorder characterized by a complex pathogenesis, by impairment social communication and interaction, and may also manifest repetitive patterns of behavior. Many studies have recognized an alteration of the immune response as a major etiological component in ASDs. Despite this, it is still unclear the variation of the function of the immune response. AIM Our aim is to investigate the levels of immunological markers in peripheral blood of children with ASD such as: regulatory B and T cells, memory B and natural killer (NK) cells. MATERIALS AND METHODS We assessed various subsets of immune cells in peripheral blood (regulatory B and T cells, B-cell memory and natural killer cells) by multi-parametric flow cytometric analysis in 26 ASD children compared to 16 healthy controls (HCs) who matched age and gender. RESULTS No significant difference was observed between B-cell memory and NK cells in ASDs and HCs. Instead, regulatory B cells and T cells were decreased (p<0.05) in ASD subjects when compared to HCs. DISCUSSION Regulatory B and T cells have a strategic role in maintaining the immune homeostasis. Their functions have been associated with the development of multiple pathologies especially in autoimmune diseases. According to our study, the immunological imbalance of regulatory B and T cells may play a pivotal role in the evolution of the disease, as immune deficiencies could be related to the severity of the ongoing disorder.